THE PARTNERS' PLACE WITHIN THE ONGOING GRANDCHILD AND LATE LIFE REPARTNERED GRANDPARENT RELATIONSHIP. (11th November 2018) - Koren, C; Lipman-Schiby, S
Abstract: With the increase in life expectancy, relationships between grandchildren and grandparents are likely to last longer. Late-life repartnering of a grandparent could affect such relationships. The aim of this presentation is to examine the experience of such relationships from the perspectives of adult grandchildren. Semi-structured qualitative interviews with a sub-sample of 20 young-adult grandchildren to grandparents who repartnered late-in life were chosen from an intergenerational family relationship study on late-life repartnering in Israel. Data was analyzed using an interpretive phenomenology approach. Grandchildren experienced change in the relationship with their grandparent, influenced by the grandparent's partner. There were grandchildren who experienced that the grandparent's partner caused a sense of distance and loss of relationship with grandparent. Others experienced that the grandparent's partner assisted in strengthening and renewing the relationship. Findings are discussed using a life course perspective. Implications for theory and practice dealing with intergenerational family relationships, are suggested.